2014
DOI: 10.1017/s0305000914000713
|View full text |Cite
|
Sign up to set email alerts
|

The production effect in memory: a prominent mnemonic in children

Abstract: The 'Production Effect' (PE) refers to a memory advantage for items studied aloud over items studied silently. Thus, vocalizing may serve as a mnemonic that can be used to assist learners in improving their memory for new concepts. Although many other types of mnemonic have been suggested in the literature, the PE seems especially appropriate for young children, as it does not involve literacy skills. The present study is a first investigation of the PE in children. In two experiments we tested five-year-olds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
74
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(91 citation statements)
references
References 58 publications
12
74
5
Order By: Relevance
“…In both Experiments 1 and 2, children successfully mapped novel words to their nonce referents. However, contrary to the majority of results reported from production studies with adults and the only existing research on the production effect with children (Icht & Mama, ), in both of the current studies, children showed better recognition for novel words that were heard rather than produced during the time of training. We call this the reverse production effect , as a counterpart to the previously coined term the production effect (MacLeod et al., ).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In both Experiments 1 and 2, children successfully mapped novel words to their nonce referents. However, contrary to the majority of results reported from production studies with adults and the only existing research on the production effect with children (Icht & Mama, ), in both of the current studies, children showed better recognition for novel words that were heard rather than produced during the time of training. We call this the reverse production effect , as a counterpart to the previously coined term the production effect (MacLeod et al., ).…”
Section: Discussioncontrasting
confidence: 99%
“…The complexity of our task might partly stem from the use of novel words and nonce referents, both of which have been shown to increase the processing load in word recognition tasks in studies with 14-month-old infants (Fennell, 2012;Fennell & Werker, 2003). While Icht and Mama (2015) found a benefit in recognition for produced items over heard items with low frequency nouns, they defined low frequency as words not likely to be found in children's expressive vocabulary (e.g., anchor, manger, cuff, pestle, razor). As such, children likely had some receptive knowledge of the infrequent word forms and their visual referents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both in infancy and beyond, studies have shown that word production and use provide a more stable, more reliable, better‐established representation than word recognition or comprehension alone (Icht & Mama, ; MacLeod, Gopie, Hourihan, Neary, & Ozubko, ; Vihman, DePaolis, & Keren‐Portnoy, ; Zamuner, Morin‐Lessard, Strahm, & Page, ). There are many reasons why this should be true, including the greater effort involved in production, which accordingly supports more robust memory or representation (Elbers & Wijnen, ) and the support that a match to a well‐practised production routine affords to the challenge of retaining novel word forms; the matching process, which becomes increasingly accessible as the lexicon grows, constructs or shapes phonological memory (Keren‐Portnoy, Vihman, DePaolis, Whitaker, & Williams, ).…”
Section: Word Production I: Item Learning and ‘Pre‐selection’mentioning
confidence: 99%
“…Even if we limited our discussion to only highly developed, referential speech gestures in older children, the overall picture is still far from simple. Producing speech has been shown to be beneficial for later recall and recognition in both adults (Zamuner, Morin-Lessard, Strahm, & Page, 2016) and children (Icht & Mama, 2015), but this production effect can be attenuated, or even reversed, due to task-, attentional-, linguistic-, and experience-related factors. In the adult literature, for example, speech learning is disrupted when engaging the speech production system in an unrelated task (Baese-Berk & Samuel, 2016).…”
Section: The Consistency Of Production Effectsmentioning
confidence: 99%